ANALISIS DIAGNOSTIK FENOMENA KEKERASAN SEKSUAL DI SEKOLAH - Nafilatul Ain; Anna Fadilatul Mahmudah; Alifia Maghfiroh Putri Susanto; Imron Fauzi (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2022)
This journal reviews the Diagnostic Analysis of the Phenomenon of Sexual Violence in Schools. This study aims to describe the portrait, analysis, and prevention of sexual violence in schools. Library research or library research is the method used. Using the literature as a kind of data collection, the materials sought are pre-selected and checked. To collect data in this study from journals, books and other sources about sexual violence against minors in schools. The results of this study are portraits, analysis, and prevention of sexual violence against children. Sexual violence in the world of education is currently being hotly discussed, sexual violence that occurs ranging from violence perpetrated by educators against students, violence perpetrated by students against teachers, and violence among peers. The occurrence of sexual violence is caused by two variables which include internal variables and external variables. Internal variables consist of psychological, biological, moral and revenge factors. Then external variables include cultural, economic, and mass media factors. Prevention of sexual violence against children in schools, namely prevention of sexual violence in schools by providing sexual violence psychoeducational outreach programs to teachers, students and parents. What the government must do to handle sexual violence in schools is to establish strict regulations governing violence against children, imposing sanctions.